Biology and Control of Indian Jujube (Ziziphus mauritiana): A Weed to Watch in Florida Pastures and Natural Areas - Brent Sellers (EDIS, 2008)
SS-AGR-307, a 3-page illustrated fact sheet by Brent Sellers, describes this large shrub native to southern Asia and eastern Africa, and which is reported in Miami-Dade, Lee, and Glades counties — it’s identification, habitat and ecology, spread, and control. Includes references. Published by the UF Department of Agronomy, August 2008.